Best Environmental Practices in the Leather Sector: a framework for circular economy initiatives based on the views of specialists and researchers - De Almeida, Ilton Marchi [UNESP]; Ribeiro Da Silva, Hermes Moretti [UNESP]; Jugend, Daniel [UNESP]; Pinheiro, Marco [UNESP] (Soc Leather Technol Chemists, 2023)
The leather industry has socio-economic relevance for producing countries. However, the standard production model has been questioned in terms of environmental aspects. Through a systematic review of the literature, this paper proposed a framework of environmental best practices and circular economy initiatives, based on the evaluations of academic authors and specialists from companies in the sector. Four dimensions were considered as criteria for evaluating environmental practices: reliability, applicability, adherence and effectiveness. The results indicate a high level of agreement on best practices, confirming the potential for generating environmental benefits, with specialists attributing values of agreements higher than those presented by the authors of scientific articles. This supports the view that more sustainable production initiatives are viable, preserving the socioeconomic importance of the sector without harming the environment. The implications of this work cover the theories and practices addressed through the consultation with the two targeted participant groups. The commonality of processes and chemical use across countries can also be seen as a critical factor for advancing the frontiers of knowledge and implementing more sustainable production processes.
Keywords: Circular economy; Leather; Waste management; Environment; Sustainability